2012
DOI: 10.3109/0886022x.2012.673466
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Hemodialysis for Active Rewarming in Severe Hypothermia: A Case Report and Review of Literature

Abstract: Deep accidental hypothermia (body temperature below 28 C) is rare. Even with modern supportive care of active external and internal rewarming techniques it is associated with a high mortality rate. We report the early and successful use of hemodialysis (HD) for active rewarming of a middle-aged alcoholic man with severe deep accidental hypothermia after failure of initial efforts of rewarming using conventional strategies. This case report and review of the literature highlights the advantages and the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…Ruttmann et al also suggested that ECMO improves the survival in severe hypothermic patients with cardiocirculatory arrest (14). However, as several case reports have mentioned, HD is a therapeutically effective and safe internal rewarming method for moderate and severe hypothermia in the absence of cardiac arrest (18,19). The advantages of HD for the treatment of hypothermia are low invasiveness, easy adjustment of the rewarming rate, and availability even in cases with a normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Ruttmann et al also suggested that ECMO improves the survival in severe hypothermic patients with cardiocirculatory arrest (14). However, as several case reports have mentioned, HD is a therapeutically effective and safe internal rewarming method for moderate and severe hypothermia in the absence of cardiac arrest (18,19). The advantages of HD for the treatment of hypothermia are low invasiveness, easy adjustment of the rewarming rate, and availability even in cases with a normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Les dernières publications [2,11] rapportent la circulation extracorporelle (CEC) comme technique de choix pour le réchauffement et la réanimation des arrêts cardiaques hypothermiques jouant dans le même temps le rôle d'assistance circulatoire. La CEC permet d'obtenir une vitesse de réchauffement de 5°C/h comme les dispositifs d'hémodia-lyse ou d'hémofiltration proposés par certains auteurs [12].…”
Section: Discussionunclassified
“…Hypotension. Haemodialysis [ 242 , 262 266 ] Adds ~2–3 °C hr -1 Not commonly used, patient must be able to increase cardiac output to perfuse the external circuit. Heparinisation required.…”
Section: Accidental Hypothermia: An Update- Part 2 In-hospital Managementioning
confidence: 99%